Renal injury and recovery in pediatric patients after ventricular assist device implantation and cardiac transplant. (24th May 2019) - Hollander, Seth A.; Cantor, Ryan S.; Sutherland, Scott M.; Koehl, Devin A.; Pruitt, Elizabeth; McDonald, Nancy; Kirklin, James K.; Ravekes, William J.; Ameduri, Rebecca; Chrisant, Maryanne; Hoffman, Timothy M.; Lytrivi, Irene D.; et al.
Abstract: Background: The use of ventricular assist devices (VADs) in children with heart failure may be of particular benefit to those with accompanying renal failure, as improved renal function is seen in some, but not all recipients. We hypothesized that persistent renal dysfunction at 7 days and/or 1 month after VAD implantation would predict chronic kidney disease (CKD) 1 year after heart transplantation (HT). Methods: Linkage analysis of all VAD patients enrolled in both the PEDIMACS and PHTS registries between 2012 and 2016. Persistent acute kidney injury (P‐AKI), defined as a serum creatinine ≥1.5× baseline, was assessed at post‐implant day 7. Estimated glomerular filtration rate (eGFR) was determined at implant, 30 days thereafter, and 12 months post‐HT. Pre‐implant eGFR, eGFR normalization (to ≥90 mL/min/1.73 m 2 ), and P‐AKI were used to predict post‐HT CKD (eGFR <90 mL/min/1.73 m 2 ). Results: The mean implant eGFR was 85.4 ± 46.5 mL/min/1.73 m 2 . P‐AKI was present in 19/188 (10%). Mean eGFR at 1 month post‐VAD implant was 131.1 ± 62.1 mL/min/1.73 m 2, significantly increased above baseline ( P < 0.001). At 1 year post‐HT (n = 133), 60 (45%) had CKD. Lower pre‐implant eGFR was associated with post‐HT CKD (OR 0.99, CI: 0.97‐0.99, P = 0.005); P‐AKI was not (OR 0.96, CI: 0.3‐3.0, P = 0.9). Failure to normalize renal function 30 days after implant was highly associated with CKD at 1 year post‐transplant (OR 12.5, CI 2.8‐55, P = 0.003). Conclusions: Renal function improves after VAD implantation. Lower pre‐implant eGFR and failure to normalize renal function during the support period are risk factors for CKD development after HT.